(untitled) (American Journal of Islam and Society, 1992)
The establishment of a new political system and social order as a result of a conscious Islamization effort is an important event in contemporary world history. The Islamic revolution in Iran and the establishment of an Islamic republic in that country in 1979 was such a landmark event. A development which may have a similar significance for the 1990s is the emergence of a formal social and political Islamization effort in Sudan following the revolution of 1989. In Sudan, the National Islamic Front led by Hasan lbrabi is working with the revolutionary regime of Omar Hassan al-Bashir in a major effort to transform Sudan on the basis of a more active adherence to Islamic ideals and standards. The Iranian and Sudanese experiences have many differences but also some important similarities. One of these is that in both cases, important intellectual leaders, the Ayatollah Khomeini in Iran and Hasan Turabi in Sudan, had been engaged in a long-term effort to define what a truly Islamic political system and social order should be. As a result, the revolutions of 1979 and 1989 brought to power groups possessing explicit conceptualizations regarding the nature of the systems to be implemented and leaders who were willing to work with governments to assist in this process of conscious Islamization. Hasan lbrabi has a long history of active involvement in Sudanese politics. By 1989 he had helped to create both an effective political organization, the Sudanese Muslim Brotherhood, and an articulated ideology of sociopolitical Islamization. The organization and the ideology provide the foundation for what was in many ways to become “Turabi’s revolution.” Abdelwahab El-Affendi, a journalist, political scientist, and diplomat, provides us with a description and analysis of this intellectual and political force. His substantial account of lhrabi’s revolution has the special benefits and difficulties of being written by “an Islamist engaged in studying the very movement within which I grew up and the general aims of which I still vehemently support.” This book becomes, as a result, a case study of a number of very different but important topics. There is the very nature and methodology of the author and the undertaking, as well as the issues raised by the content of ...